Pathoanatomy of shoulder instability in collegiate female athletes - Patzkowski, J. C.; Dickens, J. F.; Cameron, K. L.; Bokshan, S. L.; Garcia, E. J.; Owens, B. D. (The American Journal of Sports Medicine, 2019)
Background: Shoulder instability has been well described in young men; however, few studies have specifically evaluated the pathoanatomy and unique spectrum of injuries in women with shoulder instability. Purpose: To describe the pathoanatomy of operative shoulder instability in a collegiate female cohort. Study Design: Case series; Level of evidence, 4. Methods: The authors performed a retrospective analysis of a consecutive series of female students at a National Collegiate Athletic Association Division I military service academy treated operatively for shoulder instability by a single surgeon between September 2008 and September 2014. Preoperative data collected included patient age, sport, mechanism of injury, number and frequency of dislocations, direction of instability, and co-occurring surgical abnormalities at the time of arthroscopy. Outcome variables included recurrent instability after surgery and need for revision. Results: Thirty-six female student athletes with an average age of 20 years (range, 18-22 years) were included. The majority of instability events were traumatic in nature (69%), and 61% of the total events were subluxations. Rugby was the most common sport for experiencing instability (7 patients), followed by obstacle course training (6 patients). Thirty-two patients (89%) reported multiple instability events, averaging 4 per shoulder. The primary direction of instability was anterior in 26, combined anterior and posterior in 7, and 3 met criteria for multidirectional instability. At the time of surgery, 26 patients (72%) had a Bankart tear, 9 (25%) had a posterior labral tear, and 5 (14%) had superior labrum anterior to posterior tears. Nine patients (25%) were found to have humeral avulsion of the glenohumeral ligament (HAGL) lesions, 7 (19%) had partial-thickness articular-sided rotator cuff tears, and only 1 patient (3%) had evidence of true attritional glenoid bone loss. Hill-Sachs lesions were found in 16 patients (44%). Recurrent instability occurred in 9 patients (25%) following arthroscopic stabilization, and revision surgery was performed in 6 (17%). Conclusion: Shoulder instability in female athletes presents commonly as multiple subluxation events. While soft tissue Bankart lesions were found in numbers equal to those in previous studies include both sexes, bony Bankart lesions were less common in women. Finally, the presence of combined anterior and posterior labral tears and HAGLs in women was more common than previously reported. Keywords female, shoulder instability, women, college, pathoanatomy